Intercostal Artery Pseudoaneurysm Formation after Irinotecan Transarterial Chemoembolization of a Spinal Metastasis from Colorectal Cancer - Natanel Jourabchi; Steven Sauk; Cheryl Hoffman; Edward Wolfgang Lee; Stephen Thomas Kee (Case Reports in Radiology)
Over the past decade, irinotecan has become one of the first-line chemotherapeutic agents used in the treatment of metastatic colorectal cancer. Recently, irinotecan has been administered transarterially in order to perform chemoembolization in the liver. In the limited number of reports available to date using this approach, serious adverse effects have not yet been reported. In this paper, we describe the formation of an intercostal artery pseudoaneurysm after transarterial chemoembolization with irinotecan-eluting beads in a patient with spinal metastasis from colorectal cancer.